2000
DOI: 10.1021/ic000477b
|View full text |Cite
|
Sign up to set email alerts
|

[2 + 3] Cycloaddition of Nitrones to Platinum-Bound Organonitriles:  Effect of Metal Oxidation State and of Nitrile Substituent

Abstract: The ligated benzonitriles in the platinum(II) complex [PtCl2(PhCN)2] undergo metal-mediated [2 + 3] cycloaddition with nitrones -ON+(R3)=C(R1)(R2) [R1/R2/R3 = H/Ph/Me, H/p-MeC6H4/Me, H/Ph/CH2Ph] to give delta 4-1,2,4-oxadiazoline complexes, [PtCl2(N=C(Ph)O-N(R3)-C(R1)(R2))2] (2a, 4a, 6a), as a 1:1 mixture of two diastereoisomers, in 60-75% yields, while [PtCl2(MeCN)2] is inactive toward the addition. However, a strong activation of acetonitrile was reached by application of the platinum(IV) complex [PtCl4(MeCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 48 publications
8
64
1
Order By: Relevance
“…If the Lewis acid is coordinated to the nitrile and strong enough, the process requires a stoichiometric amount of Lewis acid and forms a stable Lewis acid-product complex. 13.3.3 Structural Aspects 13.3.3.1 X-Ray Diffraction X-Ray data of many 1,2.4-oxadiazoles confirms that the ring is planar [149][150][151][152][153][154].…”
Section: Theoretical Aspectsmentioning
confidence: 97%
“…If the Lewis acid is coordinated to the nitrile and strong enough, the process requires a stoichiometric amount of Lewis acid and forms a stable Lewis acid-product complex. 13.3.3 Structural Aspects 13.3.3.1 X-Ray Diffraction X-Ray data of many 1,2.4-oxadiazoles confirms that the ring is planar [149][150][151][152][153][154].…”
Section: Theoretical Aspectsmentioning
confidence: 97%
“…In the course of our studies on metal-mediated nucleophilic additions and cycloadditions to isonitriles RNC, [9] and upon further extension of our project on cycloadditions to ligated nitriles RCN, [10,11] we have succeeded for the first time in performing the [2+3] cycloaddition of an allyl-anion-type dipole, that is, a nitrone, to coordinated isonitriles, isolating and characterizing novel carbene complexes derived from the cycloaddition of both acyclic and cyclic nitrones. Details of the results obtained are elaborated in this article.…”
Section: R}a C H T U N G T R E N N U N G (C Nr)a C H T U N G T R E N mentioning
confidence: 99%
“…22,23 Two relatively stable aryl nitrile oxides, i.e., 2,4,6-Me 3 C 6 H 2 CNO and 2,4,6-(MeO) 3 C 6 H 2 CNO, 27 have been chosen as dipoles. The reaction between [PtCl 4 (EtCN) 2 ], exhibiting moderate solubility in CH 2 Cl 2 , and the nitrile oxides in a molar ratio of 1:4 proceeds smoothly in a suspension at room temperature and is complete after 1 day (Scheme 1), and the final products were isolated in good yields.…”
Section: Ndc(et)ondccmentioning
confidence: 99%
“…20 A few years ago, within the framework of our continuous project on reactions of metal-activated nitriles (this topic has been reviewed by two of us 20 ), it was found that the platinum(IV) center in [PtCl 4 (RCN) 2 ] complexes provides sufficiently strong activation of the nitriles to assist the facile [2 + 3] cycloaddition between RCN ligands and various nitrones (R 1 )(R 2 )Cd(R 3 )-N + O -to achieve the first examples of ∆ 4 -1,2,4-oxadiazoline complexes [PtCl 4 (∆ 4 -1,2,4-oxadiazoline) 2 ]. 22,23 In this work, we endeavored to extend the [2 + 3] cycloaddition of complexed RCN species from nitrones to nitrile oxides. The main goals of this work are the following ones: (i) to determine whether the results disclosing the enhanced reactivity of Pt(IV)-bound nitriles are specific for dipoles of allyl anion type, 24 e.g., nitrones, or the reactions can be spread out to dipoles of the propargyl/allenyl anion type, 24 e.g., nitrile oxides; (ii) to develop a general route to 1,2,4-oxadiazoles which is based on the [2 + 3] cycloaddition between the metal-activated nitriles and nitrile oxides and to perform the synthesis under mild conditions, thus preventing the nitrile oxides from dimerizing.…”
Section: Introductionmentioning
confidence: 99%